Austrostigmaeus gen. n. (Acari: Prostigmata: Stigmaeidae), with the description of a new species from Australia - Fan, Qing-Hai; Beard, Jennifer J. (Zootaxa, 2006)
A new genus, Aust rostigmaeu s is proposed for a new species, A. walter i , from Western Australia. Aus trostigmaeu s is similar to Pilonychiopu s Meyer and Neilstigm aeus Gerson & Meyer in the absence of leg tarsal claws and the presence of a developed arolium. Comparative characters for separating Aust rostigmaeu s gen. n., Gymnostigmaeu s Ehara & Ueckermann, Neilstigmaeu s Gerson & Meyer, Pilonychiopu s Meyer and Su m mersiell a Gonzalez-R. are given. Both adult sexes and the deutonymph female are described and illustrated.